Pengaruh Bermain Alat Musik Angklung Terhadap Kemampuan Mengenal Konsep Bilangan Pada Anak Usia 5-6 Tahun Di TK Negeri Pembina 3 Pekanbaru - Tus Sakinah, Mardiah; Nurlita, Nurlita; Risma, Devi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of learning that introduces children to the concept of numbers from an early age is also very important. Therefore, it is essential to have an engaging activity and be capable of offering comprehension to youngsters in the stage of becoming familiar with the idea of numerals. Angklung represents a heritage Indonesian musical device originating from the Sunda region, crafted from bamboo and produced by the technique of shaking so that the bamboo tubes strike each other to generate tones. Conventional angklung musical play can encourage multiple dimensions of early childhood growth. By engaging in play, youngsters will enhance their abilities and proficiencies in an enjoyable manner. The aim of this research is to portray the procedure and outcomes of angklung instrument performance activities to strengthen the capacity to identify numerical concepts and to examine whether practicing angklung instruments can elevate the capacity to identify numerical concepts for children aged five to six years. The research approach applied is the experimental approach using a single-group pretest design. Specifically, by administering a pretest prior to treatment and a posttest following treatment. The findings of data evaluation indicated that prior to treatment, the mean accomplishment of identifying the concept of numbers among children aged five to six years at State Kindergarten Pembina 3 Pekanbaru was merely 145 (45.31%) out of the ideal score of 320, categorized as beginning to progress (MB). After providing the Angklung Play medium, it achieved a score of 244 (76.24%) out of an ideal score of 320, thus the capacity to identify the concept of numbers in children is classified as undergoing progress in line with expectations (BSB).